Fine ceramics (advanced ceramics, advanced technical ceramics). Test method for determination of phenol oxidative decomposition performance of semiconducting photocatalytic materials by quantitative analysis of total organic carbon (TOC). (16th September 2019) - British Standards Institution,
No abstract available